Influence of Ovarian Tissue Size on Follicle Recruitment Through PTEN Pathway due to Post-Vitrification Cryoinjury - Fajar Akbar Ramadhan; Shofwal Widad; Muhammad Lutfi (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2026)
Background: The health of the reproductive organs is one of the most essential things in humans for maintaining offspring. However, loss of fertility or infertility can occur in a person as a result of the effects of cancer treatment. The frozen method of the ovarian cortex is the most widely used technique for fertility preservation, such as in cancer patients. The frozen storage process is categorized into several phases, namely: (1) vitrification, which involves solidifying the aqueous environment of cells or tissue into a non-crystalline glass phase; (2) slow freezing; (3) dry preservation; and (4) nonfreezing storage below zero degrees. Recently, research that specifically discusses the impact of frozen storage, especially cryoinjury, on follicle recruitment in ovarian tissue has been limited. It is necessary to conduct research on the effect of cryoinjury on follicle recruitment via the PTEN pathway in various sizes of ovarian tissue after vitrification.Objective: To determine the effect of ovarian tissue size on follicle recruitment through the PTEN pathway due to post-vitrification cryoinjury.Methods: Goat ovarian cortex tissue samples were divided into fresh and post-vitrification groups. Ovarian tissue is grouped according to the sizes 10x10x1 mm, 5x5x1 mm, and 2.5x2.5x1 mm. The number and proportion of follicles and PTEN protein expression are outcome parameters.Results: A total of 412 follicles were found in all treatment samples, with details of 301 follicles found in the fresh samples and 111 follicles found in the vitrified samples. The total number of follicles in vitrified samples (mean rank: 11.56) showed a significantly lower number (P < 0.05) when compared with fresh samples (mean rank: 25.44). Regarding PTEN expression, the number of follicles expressing PTEN was lower in vitrified tissue. This shows a decrease in the number of follicles, which inhibits follicle recruitment in the ovarian cortex. The number of positive primordial follicles in vitrified samples (mean rank: 12.61) decreased significantly (P < 0.05) compared to fresh samples (mean rank: 24.39).Conclusion: There is an effect of various sizes of ovarian on follicle recruitment through the PTEN pathway due to cryoinjury after vitrification and a relationship between changes in PTEN antibody expression in the PI3K-PTEN-Akt pathway and changes in the percentage of primordial follicles after PTEN vitrification.